Grief, sorrow, and Affliction in the Glorious Qur’an - خليفة سلمان طلال (Al-Adab Journal, 2018)
The present research aims at achieving more than one objective. First , it investigates the concepts of greet, sorrow, and affliction, each being a characteristic of a human being, secondly, it applied is the techniques of the semiotic method in analyzing texts, in order to study the semiotic signals signifying grief, sorrow, and affliction in the Qur’an. Thirdly, the research aims at dividing these signals or maskers into semantic fells according to how these have appeared in the texts analyzed in accordance with the semiotic method. The theoretical background of the present research introduces the nation of excitement in the human being from a psychological viewpoint. It also shows how excitement causes weakness in activity, energy, heartbeats, and how it leads to suffering, pain, and fatigue. The research is of their ports. Part one discusses the nation of ’grief’ in the Qur’an; showing the semiotic markers of one’s grief. These are forty-two markers which we have divided semantically according to their reference in the texts. Part Two handles the semiotic markers signifying ’sorrow’ in the Qur’an; these are four. Part three studies the semiotic markers signifying ’affliction’. We have, then, divided the sorrowmarkers into semantic units as referred to in the Qur’an. The Conclusion Summaries the results arrived at and offers some recommendations.